A rare case of malignant pancreatic non-functional neuroendocrine tumor presenting as huge abdominal lump - Saxena, Pradeep; Bhardwaj, Swastik; Sutrave, Tarun; Lalchandani, Ankit (International Surgery Journal, 2022)
We present a case of an exceptionally large size non-functioning pancreatic neuroendocrine tumor (PNET) in a young female. The tumor occupied the whole abdomen and pelvis and was clinically masqueraded as an ovarian tumor. Imaging with contrast enhanced CT scan and magnetic resonance imaging of the abdomen aided in preoperative diagnosis of origin of the tumor from the pancreas. Distal pancreatectomy with splenectomy and left hemicolectomy was done. Primary colocolic anastomosis was done for reconstruction. Postop course was uneventful, and patient was discharged with advice to undergo adjuvant chemotherapy. Surgical excision of large size locally advanced non-functional PNET should be done with curative intention/ to treat symptoms and improve patient survival